Cucurbita pepo var. Scallop seedlings response to phosphoric fertilization (2011)
Cucurbita pepo var. Scallop is a very vigorous crop from warm climate areas which outstands for the particular shape of its fruits with a festooned edge. Mineral nutrient supply is one of the environmental factors that influence mostly its growth. The aim of this paper was to evaluate the effect of different doses of phosphorus on yield. This trial was carried out in the Experimental Unit of Agronomy Faculty – UNCPBA, in Azul in the Argentinian Wet Pampa. The treatments were: control without fertilization, 100, 200, 300, 400 and 500 kg of ammonium phosphate. The crop started from seedlings with root ball which were transplanted on 15/11, on camlets covered with orange mulching, not irrigated and with a density of 20,000 plants/ha (2 x 0.5 m). The trial covered a total area of 1.488 m2. The trial was designed under a model of completely randomized blocks. General average yield was 48,410 kg·ha-1. The greatest total yield in t·ha-1 was obtained with the application of 300 kg·ha-1 of ammonium phosphate. The number of fruits obtained in treatments 3, 4 and 5 showed similar response, but differed from that of the other doses of 100 and 500 kg·ha-1.